Socioeconomic Factors and Asthma Control in Children - Cope, Shannon F. (Pediatr Pulmonol, 2008)
OBJECTIVES: The objective of this study was to evaluate the association between socioeconomic factors and asthma control in children, as defined by the Canadian Pediatric Asthma Consensus Guidelines. PATIENTS AND METHODS: Cross-sectional data from a completed study of 879 asthmatic children between the ages of 1 and 18 residing in the Greater Toronto Area were used. The database included data on demographics, health status, asthma control, and health-related quality of life. Stepwise forward modeling multiple regression was used to investigate the impact of socioeconomic status on asthma control, based on six control parameters from the 2003 Canadian Pediatric Asthma Consensus Guidelines. RESULTS: Only 11% of patients met the requirements for acceptable control, while 20% had intermediate control, and 69% had unacceptable asthma control. Children from families in lower income adequacy levels had poorer control. CONCLUSIONS: Disparities in asthma control between children from families of different socio-economic strata persist, even with adjustment for utilization of primary care services and use of controller medications.